Optimal assets management of a water distribution network for leakage minimization based on an innovative index. (March 2020) - Cavazzini, Giovanna; Pavesi, Giorgio; Ardizzon, Guido
Highlights: Reduction of leakage is a priority since it increase cities resiliency and sustainability. A management strategy based on an innovative index is proposed. The strategy was verified by optimization analyses on the model of a real district network. Abstract: Leakage reduction in water distribution networks is an absolute priority and several pressure management strategies have been proposed in the literature to tackle this issue. However, the definition of an effective relationship between leakage and relevant and measurable parameters still represents a challenge. This paper presented a novel performance parameter, the Leakage Performance Index (LPI), to minimize leakages starting from pressure and flow rate measurements. This parameter creates a ranking among the different nodes in the network, by properly weighting the pressure of each node with the output flow from the node in order to focus the pressure management strategy on those nodes whose impact, in terms of leakage, is expected to be greater. To verify the effectiveness of the proposed LPI, a model of an existing water distribution district in Italy was developed in EPAnet and validated by comparison with experimental results. The valve settings of the model were then used as variables of time-dependent optimization procedures aimed at minimizing different objective functions. Different scenarios were considered by varying the minimum guaranteed pressure at the customer points. The LPI minimization strategy was efficient insofar as it indirectly minimized the leakages, achieving the same results of the leakage minimization strategy.